PROSES PRODUKSI LAGU “PEACE” DI CITRANALA ART STUDIO - Halawa, Apostolikum Kristian Halawa; Wiyati, Wahyu Sri; Irawan, Ricky (UPT Pusat Penerbitan LP2MPP ISI Denpasar, 2024)
This research aims to find out the procedures, processes and utilization of tools in the production process of the song